The role of prevention supported by innovations and implementations in increasing the safety of people staying in water areas. - Ostrowski, Andrzej; Stanula, Arkadiusz; Małodobry, Zbigniew (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The most common causes of drowning are the attitudes and behavior of people swimming, drinking alcohol, not following the rules of safe bathing, disregarding regulations, regulations, prohibitions and orders, as well as low level of swimming skills, insufficient risk assessment skills and thoughtlessness.The research material included legal acts in the field of safety in water areas, drowning statistics, subject literature and publications on the Internet about investments in the functioning of water sports in Poland, and the method was the reading of official documents (acts, regulations, orders), subject literature in the field of rescue water and analysis of investments in swimming and bathing facilities.